SI AND MG ISOTOPE FRACTIONATIONS IN MELILITE IN COARSE-GRAINED CAIS MEASURED BY SIMS - Sugiura N.; Mizuno T.; Ushikubo T.; Hiyagon H. (My University, 2004)
Si and Mg isotopic compositions of melilite in three coarse-grained CAIs were measured by SIMS. Isotopic compositions of these elements were fractionated (1.0 to 2.9 ‰/amu for Si and 4.6 to 9.6 ‰/amu for Mg) relative to terrestrial values. These fractionations are similar to those reported for bulk CAIs (Clayton et al., 1988) and suggest that coarsegrained CAIs were formed by evaporative loss of some Si and Mg from high-temperature condensates as proposed by Grossman et al. (2000). No significant zoning of isotopic fractionations was observed in these CAIs. This suggests that the evaporative loss of these elements from CAIs were slow compared with diffusive homogenization and also suggests that evaporative loss ceased early before crystallization of Mg-rich melilite.
Keywords: CAI; Mg; Si; isotope fractionation; SIMS